Impact of eco-innovation and sustainable tourism growth on the environmental degradation: the case of China. Issue 3 (25th December 2023) - Chau, Ka Yin; Lin, Chen-Hsien; Tufail, Bushra; Tran, Trung Kien; Van, Le; Nguyen, Tran Thai Ha
Abstract: Climate complexities and global warming have made sustainable development a customary topic in environmental literature. Since then, various diggings have been happening in academia. Amongst them tourism and eco-innovation receives the heap due to its contribution to economic development. The study, thereby, examines the impact of tourism, economic growth and eco-innovation on environmental degradation in China. The secondary data has been extracted from World Development Indicators (WDI) database from 1988 to 2020. The nexus among the variables have been examined using Nonlinear Autoregressive Distributed Lagged (NARDL) model. Findings reveal that international tourism receipts, expenditures and number of tourist arrival, GDP, national income and inflation are positively correlated with environmental degradation, while sustainability-oriented eco-innovation is related negatively in case of China. This study has provided help to the regulators while developing new policies regarding environmental degradation by controlling emissions from economic and tourism development and using sustainability-oriented eco-innovation.